If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -4(0.25 + 0.5x) = 1 -2x + (0.25 * -4 + 0.5x * -4) = 1 -2x + (-1 + -2x) = 1 Reorder the terms: -1 + -2x + -2x = 1 Combine like terms: -2x + -2x = -4x -1 + -4x = 1 Solving -1 + -4x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 1 + 1 -4x = 1 + 1 Combine like terms: 1 + 1 = 2 -4x = 2 Divide each side by '-4'. x = -0.5 Simplifying x = -0.5
| 15p+7q+5p-4q= | | (1-7i)-(1-5i)= | | 5t-3=7 | | X/18+1=-3 | | (a^8b^2)(a^6b^8)= | | 4x-6x=x-9 | | b=85+(10+7)w | | 10x/5x-1=5+2/5x-1 | | 7x-(-4)=54 | | 7(r-1)-3=2r+5 | | -7(n+7)=4n-16 | | 4x+9-x= | | ln(4-2x)+ln(9-3x)=21n(x+1) | | 2(9x+5)=-26 | | 3z+1/4=4z+7/4 | | 86=-70+13x | | 2b+4028=51514 | | 17+-5= | | -2(4x+2)=12 | | 5x-x+2=2x+2x+2 | | 2(2x+30)+4x=360 | | (2-4i)+(1-4i)= | | 0=x^2-1 | | 11b-2b= | | 13+(-6n)+(-15)+(-5n)= | | 1.1x+-5.4=-10 | | 5/9x=5/3 | | 1/5x+2/5x+3=18 | | (5-8*2)+12=-54 | | 11-2(3m-10)=6(4-m) | | x/-3+2=7 | | 10x=25x-3 |